Efficacy, safety, and tolerability of plecanatide in patients with irritable bowel syndrome with constipation: results of two phase 3 randomized clinical trials. (May 2018) - Brenner, Darren M.; Fogel, Ronald; Dorn, Spencer D.; Krause, Richard; Eng, Paul; Kirshoff, Robert; Nguyen, Anhthu; Crozier, Robert A.; Magnus, Leslie; Griffin, Patrick H.
Abstract : OBJECTIVES: Two identical, phase 3, randomized, double‐blind, placebo‐controlled trials evaluated the efficacy and safety of plecanatide in patients with irritable bowel syndrome with constipation (IBS‐C). METHODS: Adults meeting Rome III criteria for IBS‐C were randomized (1:1:1) to placebo or plecanatide (3 or 6 mg) for 12 weeks. The primary efficacy end point was the percentage of overall responders (patients reporting ≥30% reduction from baseline in worst abdominal pain plus an increase of ≥1 complete spontaneous bowel movement (CSBM)/week from baseline in the same week for ≥6 of 12 treatment weeks). Safety was assessed by adverse events (AEs). RESULTS: Overall, 2189 individuals were randomized across the two studies and 1879 completed the studies. Demographic and baseline characteristics were similar across treatment groups and between studies. The percentage of overall responders in Study 1 was 30.2% and 29.5% for plecanatide 3 and 6 mg, respectively, vs. 17.8% placebo ( P < 0.001 for each dose vs. placebo), and in Study 2 was 21.5% ( P = 0.009) and 24.0% ( P < 0.001) for plecanatide 3 and 6 mg, respectively, compared to 14.2% for placebo. The percentage of sustained efficacy responders (overall responders plus weekly responders for ≥2 of last 4 weeks of the 12‐week treatment period) was significantly greater for both doses of plecanatide vs. placebo across both studies. All secondary end points (stool frequency/consistency, straining, abdominal symptoms) showed statistically significant improvements compared with placebo. The most common AE was diarrhea (3 mg, 4.3%; 6 mg, 4.0%; placebo, 1.0%). Discontinuation due to diarrhea was infrequent (3 mg, 1.2%; 6 mg, 1.4%; placebo, 0). CONCLUSIONS: Plecanatide significantly improved both abdominal pain and constipation symptoms of IBS‐C with minimal associated side effects and high levels of tolerability.